2007
DOI: 10.2320/matertrans.mra2007127
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Method for Manufacturing Iron Foam Using Gases Generated by Reduction of Iron Oxide

Abstract: A new method for manufacturing iron foam using CO and CO 2 as foaming gases was studied. This method consists of three stages: (1) mixing powders of pure iron, graphite, and hematite; (2) preparing the precursor by cold pressing the mixed powders; and (3) foaming by heating the precursor at temperatures between the liquidus and solidus in the Fe-C binary system. Molten iron containing carbon is foamed by gases generated by a reduction reaction. Optimizations of both the composition of the precursor and the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Therefore, new foaming processes have been suggested for iron-based materials. One was introduced in 2007 by Murakami and consists of foaming by CO and CO 2 , which are formed by reactions between carbon and Fe 2 O 3 in a heated Fe-Fe 2 O 3 -C mixture [41]. Another process was published in 2014 by Murakami and consists of foaming of a FeO-Fe 2 O 3 -CaO-Al 2 O 3 slug and a subsequent reduction of the obtained porous oxide [40].…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, new foaming processes have been suggested for iron-based materials. One was introduced in 2007 by Murakami and consists of foaming by CO and CO 2 , which are formed by reactions between carbon and Fe 2 O 3 in a heated Fe-Fe 2 O 3 -C mixture [41]. Another process was published in 2014 by Murakami and consists of foaming of a FeO-Fe 2 O 3 -CaO-Al 2 O 3 slug and a subsequent reduction of the obtained porous oxide [40].…”
Section: Introductionmentioning
confidence: 98%
“…Foaming is driven by the CO and CO 2 generated by the reduction of the iron oxide by carbon. [37] Iron foams with porosity of approximately 55 % were obtained using the process. An alternative method uses less expensive powder (i.e., water atomized powders) and a slip reaction sintering process to produce steel foams with compressive strength significantly higher than that of aluminum foams.…”
Section: Reviewsmentioning
confidence: 99%
“…in the form of three-dimensional (3-D) Fe-based foam, which is expected to offer particular advantages as an advanced structural and functional material owing to its 3-D structure, low cost, low weight, large specific surface area, and high impact absorbability, along with high mechanical strength and high stiffness-to-weight ratio. [8][9][10] Only during recent years, several studies have been reported on the processing and properties of Fe foam manufactured by a variety of processes, such as powder metallurgy, [6,11] gas foaming, [12] slag foaming, [13] hollow spheres, [14] and lotus-type [15,16] most likely for structural applications. Therefore, there still exists considerable demand for developing Fe foams with controlled porosity, pore size, and strut width to be potentially applied as a 'platform' material for various functional fields described above.…”
Section: Introductionmentioning
confidence: 99%